2018
DOI: 10.1071/rd17412
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and the transition dairy cow

Abstract: The transition from pregnancy to lactation (i.e. the transition period) is a time of significant metabolic challenge, with a several-fold increase in a cow’s requirement for energy, protein and minerals within days of calving. A successful transition involves the initiation and coordination of changes in multiple tissues that facilitate the provision of these nutrients to the cow and, more specifically, to the mammary gland, often at the considerable expense of other tissues. Failure to coordinate the necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 182 publications
2
54
0
Order By: Relevance
“…Schuberth, 2 and Ch. Kühn 6,11 diseases also show metabolic disorders (Raboisson et al, 2014;Vercouteren et al, 2015;Mostert et al, 2018), and several authors have demonstrated the connection between the capacity of immunological defense strategies and metabolic regulatory mechanisms (Overton and Waldron, 2004;Roche et al, 2017;Wankhade et al, 2017). In the future, it will be important to reconcile economic efficiency and ethical requirements by breeding cows that are high-yielding as well as healthy and long-lived.…”
Section: Introductionmentioning
confidence: 99%
“…Schuberth, 2 and Ch. Kühn 6,11 diseases also show metabolic disorders (Raboisson et al, 2014;Vercouteren et al, 2015;Mostert et al, 2018), and several authors have demonstrated the connection between the capacity of immunological defense strategies and metabolic regulatory mechanisms (Overton and Waldron, 2004;Roche et al, 2017;Wankhade et al, 2017). In the future, it will be important to reconcile economic efficiency and ethical requirements by breeding cows that are high-yielding as well as healthy and long-lived.…”
Section: Introductionmentioning
confidence: 99%
“…In the transition period -three weeks prepartum up to three weeks after calving -there are major adaptive changes (physiological, metabolic and nutritional) characterizing the final period of gestation and the beginning of lactation. The way these changes occur and how they are managed are of great importance because they are closely linked to the performance of lactation, the occurrence of after calving diseases (clinical and subclinical) and reproductive efficiency, significantly affecting the profitability of the herds (Roche et al, 2018).…”
Section: Transition Period and Effects On Reproductionmentioning
confidence: 99%
“…The occurrence of negative energy balance, high concentrations of fatty acids, b-hydroxybutyrate and triacylglycerol in the liver, coincide with the resumption of ovarian activity, development of follicles that supply oocytes for fertilization and uterine involution and remodeling (Roche et al, 2018). Thus, together, these processes and metabolic states can affect pre and post-ovulatory reproductive function (Luttgenau et al, 2016).…”
Section: Transition Period and Effects On Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationships between body condition, metabolic status, liver function and reproduction, have been studied extensively in periparturient and early lactation dairy cows (Roche et al 2007(Roche et al , 2009(Roche et al , 2011(Roche et al , 2013(Roche et al , 2018LeBlanc 2012;Sundstrum 2015;Overton et al 2017). In the period before calving, there is an increase in glucose demand for foetal growth and after calving glucose is required for milk production.…”
Section: Introductionmentioning
confidence: 99%